2016
DOI: 10.1289/ehp.1509902
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Prevalence in Relation to Serum Concentrations of Polychlorinated Biphenyl (PCB) Congener Groups and Three Chlorinated Pesticides in a Native American Population

Abstract: Background:Exposure to persistent organic pollutants (POPs) is known to increase risk of diabetes.Objective:To determine which POPs are most associated with prevalence of diabetes in 601 Akwesasne Native Americans.Methods:Multiple logistic regression analysis was used to assess associations between quartiles of concentrations of 101 polychlorinated biphenyl (PCBs) congeners, congener groups and three chlorinated pesticides [dichlorodiphenyldichloroethylene (DDE), hexachlorobenzene (HCB) and mirex] with diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…Our findings on the positive relationships between POPs and T2D are consistent with a number of previous cross-sectional studies [ 10 , 11 , 13 , 15 , 35 , 42 ]. Lee et al found a strong dose–response relationship between serum concentrations of six POPs, including DDE and PCBs, and T2D in a study among the US general population [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings on the positive relationships between POPs and T2D are consistent with a number of previous cross-sectional studies [ 10 , 11 , 13 , 15 , 35 , 42 ]. Lee et al found a strong dose–response relationship between serum concentrations of six POPs, including DDE and PCBs, and T2D in a study among the US general population [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, other potential risk factors such as an exposure to environmental contaminants may also contribute to the high rates of T2D [ 6 ]. Epidemiological studies have confirmed positive associations between exposure to certain persistent organic pollutants (POPs) including polychlorinated biphenyls (PCBs) and dichlorodiphenyldichloroethylene (DDE), and T2D in general [ 7 , 8 , 9 , 10 , 11 , 12 ] and among Indigenous populations [ 13 , 14 , 15 , 16 , 17 , 18 ]. First Nations were reported to be exposed to higher levels of PCBs and DDE compared to the general Canadian population through traditional food, in particular, fish consumption [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Everett et al (26), total TEQ, as well as individual dioxin isomers such as 1,2,3,6,7,8-HxCDD, OCDD, 2,3,4,7,8-PeCDF, PCB169, 118, and 156, were significantly associated with increased OR of DM, among participants of the 1999 -2004 NHANES. Aminov et al (27) reported that the linear trend for the association between DL-PCBs TEQ (sum of 6 isomers) and prevalent diabetes was significant (P = 0.010) among 601 native Americans, after adjustment for the concentrations of three organochlorine (OC) pesticides.…”
Section: Decreasing Trend Of Dioxin Concentra-tions In Blood and Serummentioning
confidence: 99%
“…These projects involved qualitative research (i.e., interviewing elders and their families in the Mohawk community of Akwesasne) about environmental impacts and the translation of these data to develop a culturally specific, integrated model of environmental health, risk, and restoration ( Arquette et al 2002 ). The Akwesasne Task Force on the Environment continues to explore the impact of PCBs on tribal health and has identified attention deficit hyperactivity disorder (ADHD) and diabetes as additional health outcomes from this exposure ( Newman et al 2014 ; Aminov et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%